Peranan intelektual - Usman Awang, 1928-; Toer, Pramoedya Ananta, 1925-2006 (Petaling Jaya : INSAN, 1987)
Role of intellectuals in society with reference to Malaysia and Indonesia; articles and poems.
Peranan intelektual /Usman Awang -- Sikap peran kaum intelektual di Dunia Ketiga / Pramoedya Ananta Toer.
In Malay.
Cover title.
Keywords: Intellectuals -- Malaysia; Intellectuals -- Indonesia; Malaysia -- Social conditions; Indonesia -- Social conditions